Effect of Vermiwash of Eudrilus Eugeniae on the Growth of Chilli Plant Capsicum Annum L.: Life Sciences-Zoology - Padmanaban, Vasanthi (International Journal of Life Science and Pharma Research, 2022)
Vermiwash is a rich combination of chemical compounds, macronutrients, and micronutrients that helps in the effective growth of plants. The current examination is focused on evaluating the effect of vermiwash produced with the help of earthworm species Eudrilus eugeniae in the growth of Chilli Plant (Capsicum annum). This study is outlined in a way to understand the impact of vermiwash in the growth of Chilli Plants, especially when they are sprayed with different proportions of the vermiwash produced by the E. eugeniae. This experiment assesses the physicochemical qualities and large-scale supplements present in vermiwash prior to the vermiwash application and a relative report was prepared on the impact of vermiwash based on different plant growth parameters. Plots were planted with C. annum plants and measurements of the studied parameters (shoot length, leaf length, and the number of leaves) were noted for 90 days with plants being observed in 20 days intervals. Our study results show that plants treated with the vermiwash exhibit a reduction in natural carbon(C) and an increase in macro-nutrients like nitrogen(N), Phosphorous (P), and Potassium (K). Also, there is an observed increase in the different growth parameters of the plant implying that vermiwash can help boost the growth characteristics of the plants which correspond to the ongoing sustainability trends. In conclusion, this study recommends that the liquid extract vermiwash prepared using the micro-organism E. eugeniae can be a powerful and quality biofertilizer that helps in increased uptake of supplements by plants resulting in higher development and more yield.